The Relationship Between Health Workers' Knowledge and the Implementation of Episiotomy Wound Care in Postpartum Mothers at the Postpartum Room of RSIA Siti Khadijah, Gorontalo City - Harismayanti, Harismayanti; Ani Retni; Faniya Ismail (Sean Institute, 2024)
Episiotomy is performed to prevent more severe damage to soft tissue due to excessive stretching forces beyond the tissue's elasticity. The episiotomy wound can become very painful, tender, swollen, and red. Patients may feel warmth in the perineal area, or may not. Sometimes, fluid may drain from the incision site. The ability to care for the wound can vary between health workers, which significantly affects the healing of the episiotomy wound in postpartum mothers. The aim of the study is to examine the relationship between health workers' knowledge and the implementation of episiotomy wound care in postpartum mothers. This research uses a quantitative method with a cross-sectional approach, with a population of 36 individuals and a sample size of 36 individuals (total sampling). The results show that health workers' knowledge is good, with proper implementation of episiotomy wound care at 94.4%, with a p-value of 0.002 < 0.05. The conclusion is that there is a relationship between health workers' knowledge and the implementation of episiotomy wound care in postpartum mothers in the postpartum room at RSIA Siti Khadijah, Gorontalo City. It is recommended for health workers to follow standard operating procedures (SOPs) in wound care to prevent infection. Patients should maintain cleanliness of the wound by changing their underwear after urination and using clean water when urinating.